A Real Effects Perspective to Accounting Measurement and Disclosure: Implications and Insights for Future Research - KANODIA, CHANDRA; SAPRA, HARESH (Journal of Accounting Research, 2016)
ABSTRACT Accounting measurement and disclosure rules have a significant impact on the real decisions that firms make. In this essay, we provide an analytical framework to illustrate how such real effects arise. Using this framework, we examine three specific measurement issues that remain controversial: (1) How does the measurement of investments affect a firm's investment efficiency? (2) How does the measurement and disclosure of a firm's derivative transactions affect a firm's choice of intrinsic risk exposures, risk management strategy, and the incentive to speculate? (3) How could marking‐to‐market the asset portfolios of financial institutions generate procyclical real effects? We draw upon these real effects studies to generate sharper and novel insights that we believe are useful not only for the development of accounting standards, but also for guiding future empirical research.